Origin of residual stress in the formation of boron nitride film by sputtering with Ar ions - Kim, HS; Park, JK; Baik, YJ; Choi, IH (AMER INST PHYSICS, 2003)
It is demonstrated that the compressive residual stress in turbostratic boron nitride (tBN) film is caused by the incorporation of Ar atoms between the gap of tBN layers. The stress of the film is measured in situ during sputter deposition at various substrate bias voltages. The variation of the stress with increasing film thickness follows that of an Ar concentration profile in the films along the growth direction. This result reveals that the interstitial Ar atoms induce the evolution of the compressive residual stress in the tBN film. Cross-sectional transmission electron microscopic images of the films are examined to explain the penetration behavior of Ar ions during the deposition. (C) 2003 American Institute of Physics.
Keywords: THIN-FILMS; INTRINSIC STRESS; C-BN; DEPOSITION; MECHANISM; TEXTURE; GROWTH